Persepsi Mahasiswa Magister Pendidikan Bahasa Indonesia Terhadap Penggunaan Edlink dalam Mendukung Pembelajaran Blended learning - Rosdiana, Eva; Sulissusiawan, Ahadi; Priyadi, Antonius Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to investigate the perceptions of master's students in Indonesian Language Education regarding the use of the Edlink platform to support blended learning. The scope of the research includes an analysis of the ease of use of the Edlink platform, the utilization of its features, learning effectiveness, interactions between students and lecturers, and the overall satisfaction with the use of Edlink as part of the technological integration in education that supports blended learning. This research employs a descriptive qualitative method, collecting data through direct observation and semi-structured interviews with 10 respondents from the Master's program in Indonesian Language Education at Tanjungpura University. The collected data were analyzed using thematic analysis techniques to gain a deeper understanding of the students' perceptions. The findings indicate that the Edlink platform offers convenience for students and provides adequate and relevant features for the course material and assignments given by lecturers. Furthermore, students consider Edlink effective in supporting learning, particularly in the context of blended learning, which combines online and offline learning activities. However, other findings suggest that the level of interaction between students and lecturers on this platform remains suboptimal, especially in the use of interactive features such as discussion forums. Nevertheless, the majority of students are satisfied with the use of Edlink as a learning platform and perceive it to have a positive role in supporting blended learning that integrates technology into education at the master's level.